2009
DOI: 10.1021/jp908238q
|View full text |Cite
|
Sign up to set email alerts
|

Improved Electron Diffusion Coefficient in Electrospun TiO2 Nanowires

Abstract: TiO 2 nanowires with a diameter of ∼150 nm, length of ∼3-4 µm, and aspect ratio of 10:1, were prepared by ultrasonically dispersing electrospun continuous nanofibers in monocarboxylic acids. The resulting pastes were used for making nanowire films on conducting glass substrates with thicknesses in the range of 500 nm to 100 µm, good adhesion, and high nanowire packing. These films were used to fabricate dye-sensitized solar cells using the D131 dye and the iodide/triiodide electrolyte. Transient photocurrent m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
120
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(130 citation statements)
references
References 31 publications
(83 reference statements)
7
120
0
Order By: Relevance
“…It was worth noting that the fiberous morphology of the samples was well preserved after the calcination. The closely contacted NPs during the calcination enabled the electrons to move easily from one grain to another and provided an effective electron transfer pathway on TiO 2 [40]. The efficient interparticle charge transfers along the well-aligned TiO 2 1D framework would benefit for the photocatalytic H 2 production [41,42].…”
Section: Phase Structure and Morphologymentioning
confidence: 99%
“…It was worth noting that the fiberous morphology of the samples was well preserved after the calcination. The closely contacted NPs during the calcination enabled the electrons to move easily from one grain to another and provided an effective electron transfer pathway on TiO 2 [40]. The efficient interparticle charge transfers along the well-aligned TiO 2 1D framework would benefit for the photocatalytic H 2 production [41,42].…”
Section: Phase Structure and Morphologymentioning
confidence: 99%
“…The electron transport time ( t ) and the electron recombination time ( r ) can be estimated by from the IMPS and IMVS plots by following Eqs. (4) and (5) [42,43]:…”
Section: Imps and Imvs Of Samplesmentioning
confidence: 99%
“…In addition, the electron diffusion coefficient (D n ) and the electron diffusion length (L n ) can be determined on the basis of film thickness (d, 4 m in this study), t and r by following Eqs. (6) and (7) [42][43][44]:…”
Section: Imps and Imvs Of Samplesmentioning
confidence: 99%
“…Park et al optimized the electrospinning process by the introduction of acetyl acetone instead of acetic acid, and the fabricated DSSCs devices based on photoelectrode composed of nanoparticles and electrospun nanorods showed improved light-electricity conversion efficiency of 3.25% [20]. It was reported that 1D electrospun TiO 2 exhibits good photovoltaic characteristics highly depending on the size and aspect ratio [21]. Therefore, engineering the microstructure and architectures of 1D electrospun TiO 2 provides opportunities on further enhancing its photovoltaic performance.…”
Section: Introductionmentioning
confidence: 99%